Toxoplasmosis complications and novel therapeutic synergism combination of diclazuril plus atovaquone - Oz, Helieh S. (Frontiers in Microbiology, 2014)
Toxoplasmosis is a major cause of foodborne disease, congenital complication and morbidity. There is an urgent need for safe and effective therapies to encounter congenital and persisting toxoplasmosis. The hypothesis was: Combination Diclazuril plus Atovaquone to exert a novel therapeutic synergy to prevent toxoplasmosis syndromes. Methods. Pregnant dams were treated with Diclazuril and Atovaquone monotherapy or combination therapy and infected intraperitoneally with Toxoplasma tachyzoites (600). Results. Infected dams developed severe toxoplasmosis associated syndrome with increases in the abdominal adiposity surrounding uteri, gansterointestinal and other internal organs and excessive weight gain. Numerous organisms along with infiltration of inflammatory cells were detected scattered into adipose tissues. Combination therapy (p< 0.01) and to a lesser extent Diclazuril (p< 0.05) protected dams from inflammatory fat and excess weight gains. This was consistent with pancreatitis development in infected dams (versus normal p< 0.05) with infiltration of inflammatory cells, degeneration and necrosis of pancreatic cells followed by the degeneration and loss of islets. Combination and monotherapy protected dams from these inflammatory and pathological aspects of pancreatitis. Infected dams exhibited severe colitis, and colonic tissues significantly shortened in length. Brush border epithelial cells were replaced with infiltration of lymphocytes, granulocytes, and microabscess formations into cryptic microstructures. Combination therapy synergistically preserved colonic structure and normalized pathological damages (p< 0.001) and to a lesser degree Diclazuril monotherapy protected dams from colitis (p< 0.05) and gastrointestinal toxoplasmosis. Other complications included severe splenitis (p<0.001) and hepatitis (p<0.001) which were normalized with combination therapy. Conclusions. Combination Diclazuril plus Atovaquone was safe and with a novel therapeutic synergism